Oxalate-induced chronic kidney disease with its uremic and cardiovascular complications in C57BL/6 mice - Mulay, Shrikant R.; Eberhard, Jonathan N.; Pfann, Victoria; Marschner, Julian A.; Darisipudi, Murthy N.; Daniel, Christoph; Romoli, Simone; Desai, Jyaysi; Grigorescu, Melissa; Kumar, Santhosh V.; Rathkolb, Birgit; Wolf, Eckhard; et al. (American Journal of Physiology-Renal Physiology, 2016)
Chronic kidney disease (CKD) research is limited by the lack of convenient inducible models mimicking human CKD and its complications in experimental animals. We demonstrate that a soluble oxalate-rich diet induces stable stages of CKD in male and female C57BL/6 mice. Renal histology is characterized by tubular damage, remnant atubular glomeruli, interstitial inflammation, and fibrosis, with the extent of tissue involvement depending on the duration of oxalate feeding. Expression profiling of markers and magnetic resonance imaging findings established to reflect inflammation and fibrosis parallel the histological changes. Within 3 wk, the mice reproducibly develop normochromic anemia, metabolic acidosis, hyperkalemia, FGF23 activation, hyperphosphatemia, and hyperparathyroidism. In addition, the model is characterized by profound arterial hypertension as well as cardiac fibrosis that persist following the switch to a control diet. Together, this new model of inducible CKD overcomes a number of previous experimental limitations and should serve useful in research related to CKD and its complications.
EVALuna2:3844